Time and Money : A Study of Labor Constraints for Female Cotton Producers in Cote d'Ivoire - Carranza, Eliana; Donald, Aletheia; Jones, Rachel; Rouanet, Léa (World Bank, Washington, DC, 2017)
A gap between male and female farmers in agricultural production, both in terms of output and productivity, has been largely documented across Sub-Saharan Africa. The Africa Gender Innovation Lab has produced a body of evidence, including the Levelling the Field report and the Cost of the Gender Gap in Agricultural Productivity report, that identified constraints women farmers face, determined the size and cost of the gap in agricultural productivity, and offered promising policy options and emerging new ideas to test. One of the key findings from the levelling the field report is that labor presents the main barrier to achieving gender equality in productivity. Across the six profiled African countries, authors observe a combination of women deploying fewer household male laborers on their plots, male laborers generating lower returns for female farmers relative to male farmers, and female farmers facing challenges in hiring effective outside labor. In this policy brief, we investigate and provide explanations for female farmers’ labor constraints through a mixed-methods study within the cotton sector of Côte d’Ivoire, as part of the Côte d’Ivoire Agriculture Sector Support Project’s efforts to increase female participation in cotton production. We first quantify the gender gap in labor usage, then look at the drivers of this gap and how they constrain women’s cotton production and productivity, and finally offer recommendations for policymakers. Several key policy considerations emerge based on our analysis, relating to labor financing and gender norms. Adopting solutions to ease female farmers’ labor constraints will not only increase their productivity, but also boost economic growth as an increasing share of the population becomes involved in the cultivation of higher-value crops.